Threat of COVID-19 Vaccine Hesitancy in Pakistan: The Need for Measures to Neutralize Misleading Narratives - Khan, Yusra Habib; Mallhi, Tauqeer Hussain; Alotaibi, Nasser Hadal; Alzarea, Abdulaziz Ibrahim; Alanazi, Abdullah Salah; Tanveer, Nida; Hashmi, Furqan Khurshid (The American journal of tropical medicine and hygiene, 2020)
Immediately after declaring COVID-19 as a pandemic, numerous wild conspiracy theories sprouted through social media. Pakistan is quite vulnerable to such conspiracy narratives and has experienced failures of polio vaccination programs because of such claims. Recently, two well-known political figures raised conspiracy theories against COVID-19 vaccines in Pakistan, stating that COVID-19 is a grand illusion and a conspiracy against Muslim countries. This theory is much discussed in the local community, supporting COVID-19 vaccine hesitancy. We urge healthcare authorities in Pakistan to take necessary measures against such claims before they penetrate to the general community. Anti-vaccine movements could undermine efforts to end the COVID-19 pandemic. We believe that ethical and responsible behavior of mass media, a careful advisory from the Pakistan Electronic Media Regulatory Authority, stern measures from healthcare authorities, effective maneuvers to increase public awareness on COVID-19, vigorous analysis of information by data or communications scientists, and publication of counter opinions from health professionals against such theories will go a long way in neutralizing such misleading claims. Because Pakistan is experiencing a large burden of disease, with a sharp rise in confirmed cases, immediate action is of paramount importance to eradicate any potential barriers to a future COVID-19 vaccination program.